Dovbnia N.P., Bondarenko L.M., Bobir D.V, Korenjuk R.A. Betweennesss by resistances to woobling and skid-ding at motion of locomotive on curves and at winding motion of wheelpair - Довбня, Н.П.; Бондаренко, Л.М.; Бобырь, Д.В.; Коренюк, Р.А. (Problems of Tribology, 2014)
Slip resistance of the surface defined band on the rail, depending on the radius of curvature of the rail head, rolling wheels on the rail and the total resistance movement of the wheel rounding off rounding and yaw wheelset. It is shown that analysis of the formulas and calculations led to the following conclusions:- work on the slip band on the rail during the motion of the wheel rounding is less than one percent of the rolling re-sistance at the actual radius and the coefficient of friction;- the calculation of the rolling resistance of the wheel on the rail rounding sliding band on the rail can be ignored, but taking into account the deterioration of rail job obviously need to consider.